Hydrometallurgical Processing Of Rare Earth Elements From Ion Adsorption Clays - Miiro, Eddy (Department of Chemical Engineering, 2024)
The surface mining and heap leaching of China's ion-adsorption rare-earth resources have caused severe environmental damage, there is a need to better understand Rare Earth leaching from Clay ore with the use of agglomerates that improve the permeability of the ore during heap leaching operation. The practice of in-situ leaching has also revealed serious environmental problems including underground contamination, mine collapses, and landslides. The performance of lixiviants in extracting Rare Earth has been compared in many studies however this has been carried out in agitated systems and the heap leach scenario is different from agitated systems. This limits the understanding of poor heap permeability and post-closure stability whereas un-agitated leaching of Rare Earth from Clay agglomerates gives a better understanding of diffusion, heap permeability, and material balance to mimic the heap leach scenario. A comprehensive understanding of the leaching mechanism is crucial for achieving high extraction efficiency with low cost and less environmental impact. A series of inorganic salts with different concentrations were employed to leach the Ion-adsorption rare earth agglomerates, and the relationship between the leaching efficiency of rare earth and reagent type was investigated in unagitated systems. This study showed that ammonium sulfate extracts less aluminum content than magnesium chloride. Even when magnesium sulfate (hydrate) extracts less aluminum (impurity in Pregnant Leach Solution) content than the other lixiviants used in the study, magnesium sulfate extracts less Rare Earth Elements (REE) compared to the other lixiviants in the same leaching time, this was an unexpected result when magnesium sulfate hydrate was used instead of anhydrous magnesium sulfate that was much more expensive (per mass) compared to the prices of the other leaching reageants. Therefore the lixiviant of preference in terms of REE extraction from ion adsorption clays in un-agitated systems is in the order (NH4)2SO4 > MgCl2.6H2O > NaCl > MgSO4.7H2O.